2015
DOI: 10.1186/s13075-015-0750-y
|View full text |Cite
|
Sign up to set email alerts
|

Low numbers of blood and salivary natural killer cells are associated with a better response to belimumab in primary Sjögren’s syndrome: results of the BELISS study

Abstract: IntroductionIn this study, we sought to address changes in blood lymphocyte subpopulations and labial salivary gland (LSG) inflammation after belimumab treatment in patients with primary Sjögren’s syndrome (pSS) and to identify predictors of response to treatment.MethodsSequential blood lymphocyte subsets and LSG biopsies were analysed between week 0 (W0) and W28 in 15 patients with pSS treated with belimumab. Systemic response to treatment was defined as a decrease in the European League Against Rheumatism Sj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 29 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…Finally, in the Belimumab in Subjects With Primary Sj€ ogren's Syndrome (BELISS) trial, good response was obtained exclusively in patients with low levels of natural killer cells in peripheral blood or the salivary glands. 44 These findings support the hypothesis of several forms of the disease. Patients with high levels of IL-12p70 in serum could have a T H 1 signature, have activation of natural killer cells both in blood and salivary glands, and be less sensitive to B cell-targeted therapy.…”
Section: Discussionsupporting
confidence: 77%
“…Finally, in the Belimumab in Subjects With Primary Sj€ ogren's Syndrome (BELISS) trial, good response was obtained exclusively in patients with low levels of natural killer cells in peripheral blood or the salivary glands. 44 These findings support the hypothesis of several forms of the disease. Patients with high levels of IL-12p70 in serum could have a T H 1 signature, have activation of natural killer cells both in blood and salivary glands, and be less sensitive to B cell-targeted therapy.…”
Section: Discussionsupporting
confidence: 77%
“…Increased BAFF serum levels also seem to be predictive of rituximab (RTX) treatment failure, suggesting a possible predictive role of BAFF serum levels in identifying a subset of patients suitable to be treated with this B-cell depleting agent [161]. On the contrary, data from a small open label study suggest that serum BAFF levels are not predictive for clinical to belimumab [162]. Although these results look very promising for personalised medicine, they have to be confirmed in larger cohorts before being helpful in daily clinical setting.…”
Section: The Predictive Value Of Baseline Baff Levels For Lymphoma Dementioning
confidence: 99%
“…This debate is important and timely, since, besides its indisputable diagnostic value,3 salivary gland histopathology is increasingly considered to be a useful tool to assess the effects of treatments in clinical trials 4 5. Furthermore, despite promising open-labelled studies and two small randomised trials,6 the two large randomised controlled trials TEARS7 and TRACTISS8 (main results of which were revealed at the 2015 American College of Rheumatology meeting) did not demonstrate the superiority of rituximab over placebo on their primary end points.…”
mentioning
confidence: 99%